1989
DOI: 10.1002/bjs.1800760831
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic sphincterotomy for bile duct stones in patients with intact gallbladders

Abstract: Endoscopic sphincterotomy was performed in 121 patients (age ranged 34-92 years; median 80 years) with intact gallbladders and bile duct stones. Clearance of the duct by basket or balloon extraction was attempted in 97 patients (80 per cent) and achieved in 93 of these patients (96 per cent). In 24 patients the duct was left to empty spontaneously and this occurred in 22 patients. Immediate complications due to endoscopic sphincterotomy occurred in five patients (two haemorrhage, two perforation, one haemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…On the other hand, in patients with gallbladder in situ undergoing ES due to gallstones in the common bile duct, symptoms of biliary origin recur in 4-21% of cases, with =15% of these requiring an open operation [9,17,28,33,35,40,43,46]. It is interesting to note that a recent randomized study [5] found a 47% rate of recurrent biliary symptoms, with 37% of these patients undergoing cholecystectomy for this reason.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, in patients with gallbladder in situ undergoing ES due to gallstones in the common bile duct, symptoms of biliary origin recur in 4-21% of cases, with =15% of these requiring an open operation [9,17,28,33,35,40,43,46]. It is interesting to note that a recent randomized study [5] found a 47% rate of recurrent biliary symptoms, with 37% of these patients undergoing cholecystectomy for this reason.…”
Section: Discussionmentioning
confidence: 95%
“…Between 75% and 90% of all patients undergoing endoscopic sphincterotomy will remain asymptomatic up to 15 years after the procedure 1419 Recurrence of biliary stones occurs in 10% of patients while reintervention for stenosis may be required in around 3% 1417 19 Recurrent stones can be successfully treated by repeat sphincterotomy in 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…19 Recurrence of biliary stones occurs in 10% of patients while reintervention for stenosis may be required in around 3% 1417 19 Recurrent stones can be successfully treated by repeat sphincterotomy in 90% of cases. Although this study did not assess long term complications, serious consequences of endoscopic sphincterotomy are sufficiently uncommon to make significant long term problems in young patients unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…They make a strong case, which many would agree with, for emergency colonoscopy being the first choice examination in any patient with massive lower gastrointestinal bleeding. Trudel et al 6 described very similar results in their series in which diagnosis was established in 50% of patients and in 28 patients treated by endoscopic coagulation, 68% were controlled.…”
Section: Emergency Surgerymentioning
confidence: 71%